1996
DOI: 10.1144/gsl.sp.1996.118.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Detailed volcanic geology of the MARNOK area, Mid-Atlantic Ridge north of Kane transform

Abstract: We present the results of a detailed study of the volcanic geology of the median valley floor of the Mid-Atlantic Ridge in two adjacent but contrasting spreading segments immediately north of the Kane transform fault, based on a high-resolution deep-towed sidescan sonar (TOBI) survey, near-bottom photographic traverses, and geochemical analyses from 28 precisely sited sets of dredge samples. This has allowed us to assess the relative importance of small (intersegment) and large (transform) boundaries on magmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 98 publications
2
25
0
Order By: Relevance
“…The largest one with a crater, at 27°22′ N, 127°39′ E, is approximately 500 m high (Figure 2b). Just west of these volcanoes, hummocky terrain (H1 in Figure 2a) similar to those often found in the axial areas of mid-ocean ridges (e.g., Lawson et al 1996) is observed. Many small conical structures less than 1 km in diameter are also observed in this area (Figure 2b).…”
Section: Results Bathymetrysupporting
confidence: 58%
“…The largest one with a crater, at 27°22′ N, 127°39′ E, is approximately 500 m high (Figure 2b). Just west of these volcanoes, hummocky terrain (H1 in Figure 2a) similar to those often found in the axial areas of mid-ocean ridges (e.g., Lawson et al 1996) is observed. Many small conical structures less than 1 km in diameter are also observed in this area (Figure 2b).…”
Section: Results Bathymetrysupporting
confidence: 58%
“…2-2). The geometry is of a draped survey performed by the RSS Charles Darwin towing the TOBI (Towed Ocean Bottom Instrument) system across the rift valley of the MidAtlantic Ridge north of the Kane transform in 1991 [Lawson et al, 1996]. A magnetic reversal pattern, in accordance with appropriate spreading rates is imposed on a 500 m thick layer, as is an area of strong magnetization at the neovolcanic axis (central anomaly magnetic high-CAMH).…”
Section: F[j D1 ] and F[b]mentioning
confidence: 99%
“…Figure 2-3: Deep-tow magnetic profile across the MAR (24°20'N) [Lawson et at., 1996]: Panels arranged as in Figure 2-2. The neovolcanic zone coincides with the magnetic high in both solutions.…”
Section: §mentioning
confidence: 99%
See 2 more Smart Citations